PENGARUH NAUNGAN TERHADAP NISBAH KLOROFIL-A/B SERTA HASIL DUA VARIETAS TANAMAN KEDELAI (Glycine max (L.) Merill) (Effect of Shade on Chlorophyll-a/b Ratio of Soybean Varieties (Glycine max (L.) Merill) Megi Darma, Nerty Soverda dan Jasminarni Lecturer at - Megi Darma; Nerty Soverda; . Jasminarni (Bioplantae, 2012)
This research aims to study the effect of shade on the ratio of chlorophyll a/b and the yield of the two soybean varieties. The experiment was conducted at the Teaching Farm Faculty of Agriculture University of Jambi, in the Village District Mendalo Jambi with altitude + 35 feet above sea level. Experiments using split plot design (Split-Plot Design) by 2 factors: the first factor as the main plot (main plot) is a shade (N) consisting of 2, ie, without shade and 50% shade. The second factor is the subplot (sub plot) soybean varieties (V) consisting of varieties Petek (tolerant) and Jayawijaya (sensitive). The variables measured were plant height, ratio of chlorophyll a/b, the number of primary branches, number of pods per plant, number of pods per plant contains, weight of 100 seeds and yield per plant. The results showed that administration of 50% shade and without shade of two varieties tested significant terhadapn plant height, ratio of chlorophyll a / b, the number of primary branches, number of pods per plant, number of pods per plant contains, weight of 100 seeds, and yield per plants, but not significantly different to the chlorophyll-a, chlorophyll-b and the ratio of chlorophyll-a / b.Keywords: Soybean, shade, ratio Chlorophyll-a / b.